Development of Web-based Mail Management Application at Sekolah Tinggi Kesehatan Al-Fatah Bengkulu - Hari, Febryan Hari Purwanto; Azka, Azka Apta Afrizal (SMART : Jurnal Teknologi Informasi dan Komputer, 2023)
Mail management in an agency or company is usually done by recording incoming and outgoing letters in an agenda book, as well as at Sekolah Tinggi Kesehatan Al-Fatah Bengkulu. But this method will require more and more agenda books and eventually accumulate in the file storage area and make it difficult when searching for letter data and files when needed for certain purposes. To solve this problem, research was carried out to develop a Web-based Mail Management Application at Sekolah Tinggi Kesehatan Al-Fatah Bengkulu. The application was successfully created using a web-based system using the MySql database so that it can be accessed from all computer networks at the Sekolah Tinggi Kesehatan Al-Fatah Bengkulu. This application can facilitate the management of incoming and dispositional letters, outgoing letters and decrees and can speed up the process of documentation and searching for archive data and letter files because documents can be viewed in pdf format.